The Effectiveness of Management Information Systems in Improving the Job Performance of Public Administration Employees – University of Zawiya (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the effectiveness of management information systems in improving employees’ job performance at the General Administration of the University of Zawia. The study adopted the descriptive-analytical approach. The study population consisted of 150 employees, while the sample included 50 respondents. A questionnaire was used as the main data collection tool. The findings showed that the level of management information systems effectiveness was high, with a mean of 3.49, and job performance was also high, with a mean of 3.72. The results also revealed a strong, positive, and statistically significant correlation between the two variables (r = 0.707). The study recommended developing technical infrastructure, enhancing training, and supporting the effective use of systems within university administration.
Keywords: Management Information Systems, Job Performance, System Effectiveness, General Administration, University of Zawia